(untitled) (Journal of the College of Basic Education, 2024)
International relations are of great importance in modern and contemporary history, as it is one of the ways through which a deep understanding of international issues can be gained, characterized by the complexity of its dimensions and the complexity of its aspects, as it represents international political, economic and cultural goals and interests. The Iraqi-Roman relations are among the important bilateral relations in the history of Iraq. Contemporary, as both Iraq and Romania sought to document and develop relations in all political, economic, cultural and partisan levels after the revolution of July 14, 1958. The study aimed to know the nature of Iraqi-Romanian relations, and to clarify how they began and developed between the two countries in the field of diplomatic relations